Diagnostic ileocolonoscopy: getting the basics right. Issue 6 (27th March 2020) - Choy, Matthew C; Matharoo, Manmeet; Thomas-Gibson, Siwan
Abstract : Proficient colonoscopy technique that optimises patient comfort while simultaneously enhancing the timely detection of pathology and subsequent therapy is an aspirational and achievable goal for every endoscopist. This article aims to provide strategies to improve colonoscopy quality for both endoscopists and patients.